Penegakan Hukum Pidana Terhadap Peredaran Barang Cukai Ilegal di Kantor Pengawasan Dan Pelayanan Bea Dan Cukai - Pattinusa, Donny; Titahelu, Juanrico Alfaromona Sumarezs; Latumaerissa, Denny (Faculty of Law Universitas Pattimura, 2025)
The Directorate General of Customs and Excise is a directorate under the Ministry of Finance of the Republic of Indonesia which is authorized to take care of customs and excise issues. One form of violation of the law in the field of export and import of goods is smuggling. Smuggling issues are always related to customs and excise. Smuggling is an interesting issue to discuss because it relates to the implementation of the duties of law enforcers and several agencies including DGCE in enforcing the law and supervising export and import activities. The research method used to examine and discuss this issue is the normative legal research method. The approaches used are the legislative approach, conceptual approach and case approach. The legal materials used include primary legal materials and secondary legal materials. The results of this study indicate that: (1) factors affecting law enforcement against the circulation of illegal excise goods at the Ambon Customs and Excise Supervision and Service Office include the development of trade practices, misuse of information technology, and public demands for the existence of supervision of goods traffic. (2) The form of criminal law enforcement against the circulation of illegal excise goods at the Ambon Customs and Excise Supervision and Service Office is enforcement in concreto, which is carried out through prosecution. The flow of enforcement consists of 3 (three) stages, namely, pre-enforcement, enforcement and post-enforcement. The content of the results of the prosecution.